INOVASI PELAYANAN PUBLIK DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Rahman, Pandi; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Public service innovation is a breakthrough in public service which is an original creative idea and adaptation and verification that can provide benefits to society. One of the agencies that plays a role in providing public services is Gunung Toar District, Kuantan Singingi Regency. The intended public service innovation is the Integrated Service Innovation System for Greeting the Citizens (SIPATEN MAWAR), the Integrated Service Innovation System via Whatsapp (SIPATEN GUWA) , and Delivery of Birth Certificate (AJAK). The purpose of creating this application is to facilitate the community in serving in Gunung Toar District. The purpose of this study is to determine the innovation of public services in Gunung Toar District, Kuantan Singingi Regency and to determine the supporting and inhibiting factors that influence it. This study uses the success attribute of innovation by Bugge at al, where there are six indicators, namely: Governance and innovation , sources of the ideas for innovation , innovation culture , capabilities. and tools (ability tools), objectivies, outcomes, drivers, and obstacles (goals, results, drivers, and obstacles), collecting innovation data for single innovation ( collecting innovation data for a single innovation ) . This type of research is qualitative research with a phenomenological approach. The collection of necessary data, both primary and secondary data, is collected through interviews, observation, documentation, then analyzed so that conclusions can be drawn from the existing research problems. The results of this study are that the existing innovations have been running well but have not been maximized because they still have several obstacles such as lack of socialization and there are still many people who do not understand technology.  Keywords: Innovation, Public Service